(untitled) (Baghdad Science Journal, 2024)
Metal complexes chrome(III), manganese(II), iron(III), cobalt(II), nickel(II), cupper(II) and zinc(II) with diazonium of 3-amino-2-chloropyridine of general formula [2-Cl-C5H3N≡N]n[MXm], where n=2 or 3 for divalent and trivalent metal, m= 4 or 6 were synthesized. The complexes have been characterized by flame atomic absorption, (C.H.N), molar conductance, magnetic susceptibility UV-vis spectra, infrared spectra,1H-NMR spectroscopy and thermo gravimetric analysis (TGA and DTA). The measurements showed that the divalent metal ion complexes (M2+) have (1:2) M:L ratio with tetrahedral geometry around metal ions while the trivalent metal ions (M3+) formed (1:3) metal: ligand ratios with octahedral geometry. Furthermore, the complex salts were displayed for antibacterial activity versus two types of bacteria Gram, positive (Staphylococcus aureus) and Gram negative (Klebsiella pneumonia). The complex 2 Mn(II) and 3 Fe(III), exhibited moderate activity against the two tested bacteria, while the complexes 1 Cr(III), 4 Co(II) 6 Cu(II) and 7 Zn(II) showed high activity .The complex 5 Ni(II) displayed moderate and weak against the type one and type two of bacteria respectively.